Conceptualizing Indigenous Cultural Ecosystem Services (ICES) and Benefits under Changing Climate Conditions in the Klamath River Basin and Their Implications for Land Management and Governance. Issue Volume 41:Issues 3(2021) (October 2021) - Mucioki, Megan; Sowerwine, Jennifer; Sarna-Wojcicki, Daniel; Lake, Frank K.; Bourque, Shawn
In the Klamath River Basin (KRB) of northern California and southern Oregon, climate-related changes, such as more intense droughts, varied and concentrated precipitation, earlier spring and later fall conditions, extreme temperatures, and decreased snowpack have contributed to increasingly unpredictable plant reproduction and harvest cycles. In this study, we explore contemporary relationships between plants and Indigenous People in the KRB, identifying benefits of cultural ecosystem services (CES) derived from Indigenous stewarding and gathering of culturally significant plants, and discuss how these services may change based on climate change observations and experiences. This study contributes to the conceptualization of Indigenous Cultural Ecosystem Services (ICES), providing a framework for the incorporation of Indigenous concepts, approaches, and perspectives into assessments of ecosystem services (ES) and, particularly, CES. It highlights the value of Indigenous perspectives and observations of climate change effects on plant reproduction and productivity, as well as their contribution to cultural ecosystem resilience and adaptation under changing climate conditions. We propose that incorporating Indigenous concepts and approaches to assessing CES and ES could lead to more holistic management decisions and better-informed climate adaptation initiatives with greater ES for all.